Coffee Trade Dynamics: The Impact of Tariff and Non-Tariff Policies in Japan and the United States - Bagus Abiyu Rahman (PT Global Digital Sains Tekno, 2026)
Purpose: This study aims to analyze the impact of tariff and non-tariff barriers on the government and export sectors, with a focus on coffee. Coffee was selected based on Indonesia's high coffee production, reaching 11.85 million bags in the 2022/2023 period, and its crucial role in international trade. Method: The research method used panel data and tabular data over the past five years from previous research. The countries studied were Japan and the United States, which are Indonesia's largest coffee importers. The analysis was conducted to examine trends in Indonesian coffee exports to these two countries in relation to applicable tariff policies. Findings: Research results show that Indonesian coffee exports to Japan and the United States have declined year over year. The primary factor contributing to this decline is the tariff policies, both tariff barriers and non-tariff barriers, imposed by the export destination countries. Implication: These findings imply that tariff policies significantly impact the competitiveness of Indonesian coffee exports. The government needs to consider trade diplomacy strategies and export market diversification to prevent dependence on a particular country from significantly endangering the sustainability of coffee exports. Originality: The uniqueness of this research lies in its focus on coffee, with case studies of exports to Japan and the United States. Using panel data from the past five years, this study provides an empirical overview of how tariff policies may influence Indonesian coffee export trends, while also opening up opportunities for further research on international trade strategies.